Effects of low intensity laser therapy on the healing of pressure injury (Research, Society and Development, 2022)
Objective: To describe the effects that contribute to the acceleration of the healing process of pressure ulcers through low intensity laser therapy and to characterize the advantages and disadvantages of low intensity laser therapy in the treatment. Methodology: This is descriptive exploratory research, which uses the Integrative Literature Review (ILR) technique. The search was carried out in the Virtual Health Library (VHL) databases: SCIELO, MEDLINE, BDENF and LILACS, by joining three DeCS, crossed with the Boolean operator AND: "Laser, Wound, Ulcer. Results: A total of 416 articles were found in the databases. By adding the criteria, the number was reduced to 93. After analyzing the research, 16 publications were selected. Discussion: It is possible to observe that several factors contribute to the effective action of low intensity laser therapy in accelerating the healing process, especially depth and nutritional factors. However, this therapy has some small disadvantages such as the dependence on the patient's self-care during treatment, corroborating the increase of sessions. Final Considerations: Therefore, among the studies analyzed there is no consensus about the number of sessions, laser power and which factors contribute to patient recovery, making studies with exemption to larger samples through randomized clinical trials necessary.